2003
DOI: 10.1034/j.1399-302x.2003.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Amended biochemical characteristics and phylogenetic position of Treponema medium

Abstract: Umemoto et al. (1997, Int J Syst Bacteriol 47, pp. 67-72) proposed spirochete strain G7201, isolated from the periodontal pocket of an adult patient, as a new species, Treponema medium. They deposited this strain in the American Type Culture Collection (ATCC) as type strain ATCC 700293T. Recently, ATCC suggested that there is a discrepancy between the previous report and the results obtained by ATCC in biochemical tests on T. medium ATCC 700293T. In this study, we re-examined and verified the biochemical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Although the relationship between periodontitis and oral treponemes has been emphasized clinically, cultivation studies of oral treponemes are limited because of the oxygen sensitivity and unique nutritional requirements of these microorganisms and the long cultivation period (7, 8). The following species of cultivable oral treponemes have been validated: Treponema amylovorum (9), T. denticola (10), T. lecithinolyticum (11), T. maltophilum (12), T. medium (13, 14), T. parvum (15), T. pectinovorum (16), T. putidum (17), T. socranskii (18), and ‘ T. vincentii ’. (The last treponeme has not been validated in a peer‐reviewed publication.…”
Section: Human Oral Spirochetesmentioning
confidence: 99%
“…Although the relationship between periodontitis and oral treponemes has been emphasized clinically, cultivation studies of oral treponemes are limited because of the oxygen sensitivity and unique nutritional requirements of these microorganisms and the long cultivation period (7, 8). The following species of cultivable oral treponemes have been validated: Treponema amylovorum (9), T. denticola (10), T. lecithinolyticum (11), T. maltophilum (12), T. medium (13, 14), T. parvum (15), T. pectinovorum (16), T. putidum (17), T. socranskii (18), and ‘ T. vincentii ’. (The last treponeme has not been validated in a peer‐reviewed publication.…”
Section: Human Oral Spirochetesmentioning
confidence: 99%
“…Oral spirochetes, generally belonging to the genus Treponema, have been found in subgingival plaque from patients with periodontal diseases (Riviere et al, 1991;Dewhirst et al, 2000). Among them, Treponema medium, an intermediate-sized treponeme, has been isolated from the subgingival plaque of patients with adult periodontitis (Umemoto et al, 1997;Nakazawa et al, 2003). Further, using a real-time PCR assay, we recently showed that the number of T. medium organisms was increased in subgingival plaque samples from deep periodontal pockets (Asai et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[formerly] G7201 [22,23] It has been proposed (C. Wyss, unpublished data) that Treponema sp. strain ATCC 700772 (OMZ 838), whose full genome sequence has recently been reported (44), as well as three other Treponema strains-OMZ 855, OMZ 856, and OMZ 857-correspond to a new species that has tentatively been named Treponema sinensis (to reflect the strain's Chinese origins) (59).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, the properties of only one T. medium strain (ATCC 700293; ex. G7201) have been reported (22,23). Thus, in the absence of data from additional strains, the precise nature of the relationship between T. medium and Treponema sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation